A percepção de treinadores da Secretaria De Estado Do Desporto e Lazer (SEDEL) sobre o processo de iniciação esportiva. - (:unkn) unknown (FEFF - Faculdade de Educação Física e Fisioterapia, 2025)
The objective of this study was to investigate the perceptions of coachesfrom the State Department of Sports and Leisure (SEDEL) regarding the processes of sports initiation, specialization, and continuity. A qualitative research approach was employed, where 11 individual sports teachers answered a questionnaire with open-ended questions. The responses were analyzed using thematic analysis, resulting in five categories: sports initiation, sports specialization, sports continuity, competition, and challenges for engagement in sports. The findings indicated that sports initiation should be broad, incorporating diverse practices and focusing on the development of motor coordination, physical abilities, and socio-educational values. Regarding specialization, teachers suggested different age ranges for starting specialization in a specific sport, varying across the sports included in the study. They expressed greater concern about competition, the increase in physical and mental workload, and emphasized responsibility and a focus on training. For sports continuity, the teachers highlighted the importance of adapting activities; however, social relationships and interest in outcomes emerged as more prominent factors in their responses. Competition was viewed as secondary during initiation but was considered important for learning and socialization. In the final category, material and physical infrastructure, along with the need for training and additional human resources, were identified as challenges for the professional practice of sports teachers.
Keywords: Iniciação esportiva; Sports Initiation; Especialização esportiva; Pedagogia do esporte; Continuidade esportiva; Sports Specialization; Sports Continuity; Sports Pedagogy; CIÊNCIAS DA SAÚDE: EDUCAÇÃO FÍSICA; .; .